Heterogeneous Returns to Education in the Labor Market - Fasih, Tazeen; Kingdon, Geeta; Patrinos, Harry Anthony; Sakellariou, Chris; Soderbom, Mans (World Bank, Washington, DC, 2012)
Since the development of human capital theory, countless estimates of the economic benefits of investing in education for the individual have been published. While it is a universal fact that in all countries of the world the more education one has the higher his or her earnings, it is nevertheless important to know the empirical returns to schooling. However, simply knowing average returns is not useful in a world of heterogeneity. This paper finds increasing returns going from the lower to the higher end of the earnings distribution, but with some important differences across regions. The returns increase by quantile for Latin America. The returns decrease by quantile for most East Asian countries, producing an overall equalizing effect. India and Pakistan demonstrate opposite results. In Ghana, the returns across the distribution are flat, while for Kenya and Tanzania education is dis-equalizing.